Cardiac Autonomic Modulation of Healthy Individuals and Patients with Chronic Obstructive Pulmonary Disease During Spontaneous and Controlled Breathing - Paschoal,Mario Augusto (2020)
Abstract Background: Lung diseases and different forms of breathing may interfere with cardiac autonomic modulation (CAM). Objective: To compare CAM in individuals with chronic obstructive pulmonary disease (COPD) with healthy individuals during spontaneous breathing (SB) and controlled breathing (CB). Methods: Cross-sectional study involving 30 individuals selected by convenience, divided into COPD group (n = 19) and control group (CG; n = 12). All participants were submitted to heart beat recordings during five minutes at rest (SB) and another five minutes during CB performed at six cycles/min. CAM was made by assessment of the heart rate variability (HRV) through time domain (TD) and frequency domain (FD). Comparisons between groups were performed by Mann Whitney test, and significance level was set at p < 0.05. Results: During SB, HRV TD and FD indices were higher in the controls than in the COPD group, respectively - RR intervals (53.2 ms versus 36.6 ms), RMSSD (42.1 ms versus 26.6 ms) (p < 0.05), total power (28322.8 ms2/Hz versus 2011.6 ms2/Hz), and high-frequency band (800.5 ms(2) versus 330.7 ms2). During CB, the CG also showed higher values for the TD parameters pNN50 (11.7% versus 5.1%), RMSSD (48.3 ms versus 26.7 ms), and SD of RRi (64.9 ms versus 44.7 ms), as well as for the low-frequency component of FD analysis (2848.6 ms2 versus 1197.9 ms2). Conclusion: COPD patients have different CAM when compared with healthy individuals during spontaneous (SB) and controlled breathing (CB).